Psychoanalysis, history, and radical ethics : learning to hear - Orange, Donna M. (Psychology and the other., 2020)
Psychoanalysis, History, and Radical Ethics: Learning to Hear explores the importance of listening, being able to speak, and those who are silenced, from a psychoanalytic perspective. In particular, it focuses on those voices silenced either collectively or individually by trauma, culture, discrimination and persecution, and even by the history of psychoanalysis. Drawing on lessons from philosophy and history as well as clinical vignettes, this book provides a comprehensive guide to understanding the role of trauma in creating silence, and the importance for psychoanalysts of learning to hear those silenced voices.